A Presentation and Classification of Pictorial Carpets of Qajar Era - Ahani, Laleh; Yaghoubzadeh, Azade; Vandshoari, Ali (Journal of History Culture and Art Research, 2017)
As one of Iranian cultural industries, carpet owns an ancient background and archaism. Primarily, it has been created due to the needs. Iranian hand-made carpet, as a symbol of Iranian art, which is culturally and nationally so important, through the years it has been a suitable bed for emanation of beliefs and credence of local artists, which its figures are projecting it. Carpets are full-view mirrors of Iranian artist’s enthusiasm, emotions, and worldview. Along with other phenomenon of the time, pictorial carpets emerged and formed in the late 18th century, following evolutions in various art fields in Iran and while enlisting new possibilities, like printing pictures and images, gained a new expression in Iranian carpet weaving. Pictorial carpets were a major group of Iranian carpets in Qajar era. Therefore, studying and analyzing this group of newly emerged carpets will explain different aspects regarding the history of carpet weaving, especially about design and figure of carpets. Illustrations in carpet weaving could be related to various cultural, social, political, and artistry issues of the era. Here, while introducing effective factors in emergence of these types of carpets, we classify the pictorial carpets based on applied themes and topics. This article introduces the underlying causes in emergence of pictorial carpets, like influencing from western culture and art, attitudes toward realism, human oriented thoughts and emergence of photography and printing and their corresponding effect.